Differential Methylation and Transcriptome Integration Analysis Identified Differential Methylation Annotation Genes and Functional Research Related to Hair Follicle Development in Sheep - Tian, Yuezhen; Yang, Xuemei; Du, Jianwen; Zeng, Weidan; Wu, Weiwei; Di, Jiang; Huang, Xixia; Tian, Kechuan (Frontiers in Genetics, 2021)
Hair follicle growth and development is a complex and long-term physiological process, which is regulated by a variety of physical factors and signal pathways. Increasing the understanding of the epigenetic regulation and function of candidate genes related to hair follicle development will help to better understand the molecular regulatory mechanisms of hair follicle development. In this study, the MeDIP-seq was used to obtain the genome-wide methylation map of the hair follicular development of Super Merino sheep in 6 stages (fetal skin tissue at 65d, 85d, 105d, 135d, 7d and 30d after birth). Combined with the results of previous RNA-sequencing, 65 genes were screened out that were both differential methylation and differential expression, including EDN1, LAMC2, NR1D1, RORB, MyOZ3, and WNT2 gene. Differential methylation genes were enriched in Wnt, TNF, TGF- beta and other signaling pathways related to hair follicle development. The BSP results and MeDIP-seq were basically consistent, indicating that the sequencing results were accurate. As a key gene in the Wnt signaling pathway, both differential methylation and expression gene identified by MeDIP-seq and RNA-seq, further exploration of the function of WNT2 gene revealed that the DNA methylation of exon 5 (CpG11 site) promoted the expression of WNT2 gene. The overexpression vector of lentivirus pLEX-MCS-WNT2 was constructed, and WNT2 gene effectively promoted the proliferation of sheep skin fibroblasts. The results showed that WNT2 gene could promote the growth and development of skin and hair follicles. The results of this study will provide a theoretical basis for further research on sheep hair follicle development and gene regulation mechanisms.